Psychological Perspectives of Single Mothers in Higher Education Institutions: Implications for Women’s Self-Empowerment - Lazaro, Cherrylyn G.; Ayro, Eufemia C.; Cruz-Vidal, Michaela Jennarine DL.; Agpoon, Evangeline I. (Future Science / FSH-PH Publications, 2025)
This study examined the psychological perspectives of single mothers employed in higher education institutions and their implications for women’s self-empowerment. Guided by Carol Ryff’s Theory of Psychological Well-Being, the research focused on five dimensions—self-acceptance, relationships with others, autonomy, purpose in life, and personal growth. Using descriptive research design, data were gathered from purposively selected 49 single mothers in Cabanatuan City through a validated 25-item questionnaire distributed via Google Forms. Findings revealed that respondents strongly agreed on self-acceptance, autonomy, purpose in life, and personal growth, while they agreed on their relationships with others. The results highlight that single mothers exhibit resilience, autonomy, and a strong sense of purpose, though they remain guarded in forming deeper interpersonal relationships. These findings imply the need for holistic empowerment initiatives that reinforce strengths in self-acceptance, independence, and growth while addressing vulnerabilities in relational support. The study concludes that empowering single mothers requires both personal development opportunities and institutional policies that recognize their dual roles as educators and sole caregivers, thereby fostering their well-being and capacity to thrive.